Results of using gas-analytical hardware-software complex to assess cardiovascular diseases - Якимчук, Вікторія Сергіївна (Eastern-European Journal of Enterprise Technologies, 2015)
The relevance of a new method based on the analysis of the chemical composition of exhaled air to assess pathological conditions of the cardiovascular system was considered. The process of detecting cardiovascular diseases is realized using the developed gas-analytical hardware-software complex, the main component of which is the selected set of electrochemical sensors of ampermetric type. Practical use of the complex has allowed to collect a database of practically healthy examinees and patients with CAD and MS. Measurement data obtained from gender-homogeneous groups were analyzed using the apparatus of statistical methods. Also, ROC-analysis: finding significant factors and their limit values of the onset of the disease investigated was used to compare the results. The results have confirmed the need to divide the examinees into age groups. The proposed method of analysis of the indicators of chemical sensors has calculated the marginal factors that show the time of tracking the studied pathology. High rates of the results and using such systems allow to improve the diagnostic process and enhance screening methods of the studied functional system. At the same time, versatility of the approach to creating such complexes offers great opportunities to improve and perform basic tasks of medicine: prevention of diseases, timely appointment of remedial measures and reducing the number of fatalities.